Dromaeosaurid tracks from the Upper Cretaceous Candeleros Formation of northwestern Patagonia provide additional data on the palaeobiology and palaeoecology of ‘raptor’ dinosaurs - Heredia, Arturo Miguel (2025)
This contribution documents several strongly asymmetrical and functionally didactyl tracks from the Cenomanian Candeleros Formation of northwestern Patagonia, Argentina. This new record includes at least six tracks preserved as concave epireliefs in medium-grained sandstone from alluvial plain deposits. Each track is approximately 10 cm long, showing impressions of digits III and IV, and a proximal impression of digit II with a separated and well-developed claw trace. This type of footprint is commonly referred to dromaeosaurid dinosaurs; however, the sickle claw impression is barely known in the track record. These tracks suggest that the trackmaker had a well-developed ungual phalanx on digit II and could rest on the substrate, possibly while was stationary. The Cretaceous dromaeosaurid record in Argentina is limited to the Neuquén Basin and includes unenlagiine dromaeosaurids. Thus, it is likely that the tracks were made by a small member of this clade, such as Buitreraptor gonzalezorum. As they are the first dromaeosaurid tracks from the Candeleros Formation, and from Patagonia, these finds enhance track diversity and provide a more comprehensive correlation between ichnological and osteological evidence from this unit. This discovery contributes to our understanding of the limited dromaeosaurid track record in Gondwana and the Cenomanian age globally.